3D Flexy Leg” Silicone-Based Prosthetic Leg / Fathinah Uzma Muhamad Musbah … [et al.] - Muhamad Musbah, Fathinah Uzma; Abu Bakar, Nurul Aisyah; Ismail, Ainur Shahira; Mohd Nazlan, Nur Dania Emylia; Aryadhi, Nazirul Najwan; Husain, Nor Azmawati (Bahagian Penyelidikan dan Jaringan Industri, UiTM Melaka, 2024)
The 3D Flexy Leg is a product specially designed for people with special needs, especially individuals who have lost their legs. This product has high-quality details that help them to walk or run comfortably and provide services to make the person adapt to the new legs by giving motivational support to them to boost their confidence in their life. It is run by a startup company called “The Steeper,” located in Kota Tinggi, Johor. It is a partnership company owned by young people who are passionate about helping special needs people. The novelty of the 3D Flexy Leg is the adjustable features that equipped this artificial leg, which the users can adjust the height according to their preferences. The second uniqueness is the material used allowed the 3D Flexy Leg to look like real legs since we use silicone; besides, silicone-based legs improved comfort levels when wearing.